Pengaruh Kompetensi Manajerial Kepala Sekolah dan Kompensasi terhadap Kinerja Guru Non-PNS pada Sekolah Dasar di Kecamatan Natal, Kabupaten Mandailing Natal - Mukti Kanaya Sidiq; Maisyaroh Maisyaroh; Novita Hanum (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study investigates the effect of principals’ managerial competence and teacher compensation on the performance of non-civil servant (non-PNS) teachers in elementary schools in Natal Subdistrict, Mandailing Natal Regency. The research employed a quantitative approach using an ex post facto design. The study was conducted in 25 public elementary schools, involving 98 non-PNS teachers as respondents. The sample was determined using a total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple regression after passing classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity). The findings indicate that principals’ managerial competence has a positive and significant effect on teacher performance. Compensation also shows a positive and significant effect on performance. Simultaneously, both independent variables significantly predict teacher performance, with an adjusted R-square value of 0.370, indicating that managerial competence and compensation jointly explain 37% of the variance in non-PNS teacher performance.